REGIONAL SOCIO-ECONOMIC CONDITIONS AS A BASIS OF PLACE BRANDING SUCCESS - Макаров, Павел; Чуб, Анна (Public Administration Issues, 2022)
This paper aims to explore how regional socio-economic conditions and organizational factors affect the success of place branding activities. The secondary purpose is to systematize place branding practice of the Russian federal subjects.We conducted a logistic regression analysis of place branding success probability versus quality of place branding organisation and regionalsocio-economic conditions.The sample is comprised of 22 federal subjects of Russia within the period of 2010 to 2021. The secondary purposeis achieved through a chronological and cartographic analysis of place branding activities. We confirmed the positive influenceof organizational factors, used as a control variable, onplace branding success, and revealed the relationships between place branding success and some socio-economic conditions ofthe federal subjects of Russia: a positive relationship with the GRP, investment, and migration; a negative relationship with the population. The relationship with the adjacency to regions, already having place brand, was not confirmed. This study contributes to place branding theory by unveiling the relationship of regional socio-economic conditions and place branding success. Thus, regional conditions are needed to take into account when predicting the place branding results. This is especially important when using branding as a typical development tool because the uniform success across all regions is unlikely.